2018
DOI: 10.3390/ijms19123853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Carbon 60 Nanoparticle Exposure to Adult Zebrafish: A Behavioral and Biochemical Approach to Elucidate the Mechanism of Toxicity

Abstract: There is a growing concern for the potential toxicity of engineered nanomaterials that have made their way into virtually all novel applications in the electronics, healthcare, cosmetics, technology, and engineering industries, and in particular, biomedical products. However, the potential toxicity of carbon 60 (C60) at the behavioral level has not been properly evaluated. In this study, we used idTracker, a multitracking algorithm to quantitatively assess behavioral toxicity induced by C60 nanoparticles (C60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
(71 reference statements)
1
27
0
2
Order By: Relevance
“…A special designed chamber equipped with infrared camera by following the method described in previous publication conducted the circadian rhythm [70]. The color preference test was conducted by a special designed device by following the method described in previous publication [71]. The short-term memory was tested by using the passive avoidance method described in our previous published paper [70].…”
Section: Methodsmentioning
confidence: 99%
“…A special designed chamber equipped with infrared camera by following the method described in previous publication conducted the circadian rhythm [70]. The color preference test was conducted by a special designed device by following the method described in previous publication [71]. The short-term memory was tested by using the passive avoidance method described in our previous published paper [70].…”
Section: Methodsmentioning
confidence: 99%
“…The predator avoidance is an innate behavior of zebrafish when it engages its predator. To test whether chronic exposure to PBZ can alter such innate behavior, we placed the predator fish convict cichlid (Amatitlania nigrofasciata) into a tank separated into two parts by using a transparent separator [ 26 ]. The test zebrafish swum away from the separator was considered as predator avoidance.…”
Section: Resultsmentioning
confidence: 99%
“…In another in vivo study conducted by Sarasamma et al [53], where C60 was exposed waterborne to adult zebrafish for 12 days at 1 and 2 ppm concentrations, respectively, and fish's behavioral alterations were measured by phenomic approach. The results showed that locomotion, novel tank exploration, aggression, shoaling, and color preference activities were significantly reduced.…”
Section: Fullerene Biological Interaction Bioavailability Toxicity mentioning
confidence: 99%